Implementasi SDGS’S dan Trihita Karana dalam Pemenuhan Tanggungjawab Sosial Perusahaan Hotel Berbintang di Badung - Jayendra, Ida Bagus Gde; Surata, I Ketut; Utama, I Putu (Tulisan Ilmiah Pariwisata (TULIP), 2023)
This research aims to analyze the understanding and implementation of Sustainable Development Goals (SDGs) and Tri Hita Karana (THK) in fulfilling corporate social responsibility at 5 star hotels in Badung Regency, Bali, namely Anantara Uluwatu Bali Resort, Jumana Bali Ungasan Resort, and also Hilton Bali Resorts. The research method uses a qualitative approach by collecting data through interviews, observation and documentation from Human Resources who are tasked with planning and implementing CSR programs in the company. The results of the research show that, for the SDGs program of the three 5 star hotels studied, all of them do not understand the SDGs, but indirectly it turns out that some of their CSR activities have been included in the 17 SDGs indicators, but their implementation has not been optimal due to a lack of knowledge and information about the program. these SDGs. And for the THK program itself, it was found that the three hotels had understood and implemented this program, this was because they were used to implementing CSR programs related to THK, especially in Bali, where THK is one of the local wisdom programs from Bali and there is also the THK Bali Foundation..